Hybrid quadrupole linear ion trap mass spectrometry : application to metabolites - Christensen, Peter (2009)
The capability of the QqQLit hybrid triple quadrupole linear ion trap mass spectrometer to profile endogenous metabolites has been assessed by the analysis of three different families of metabolites; nucleotides from bacteria and N-acyl ethanolamines and N-acyl glycerols from rat tissues. Mass spectrometry methods were developed based on employing a survey scan, either precursor ion or neutral loss, coupled with full product ion spectra. This approach identified families of metabolites with a common structural core and provided the structural information for the reliable identification of known and unknown metabolites. By targeting structural similarities, this approach has opened the window of metabolites that can be profiled beyond the constraints of available references standards. A method to profile phosphate containing endogenous metabolites, particularly nucleotide metabolites, was based on the identification of the phosphate moiety following collision induced dissociation. Employing a precursor ion scan, this approach was successfully applied to the analysis of nucleotides in bacterial samples Escherichia coli MG 1655 and Pseudomonas aeruginosa. A more comprehensive profile of nucleotides was observed compared to targeted approaches. Furthermore, a considerable number of additional analytes were identified which were unlikely to be nucleotides and probably result from other endogenous phosphate containing metabolites, demonstrating the scope of the approach outside nucleotides alone. The use of this methodology was also successful in the profiling ofN-acyl ethanolamines and N-acyl glycerols. Targeting core structures common to each family of metabolite, the ethanolmine and glycerol moiety, precursor ion and neutral loss survey scans were successfully employed in identifying a wider number of these metabolites in various rat tissues than previously reported. The profile of rat testi was notably different from other tissues investigated due to the presence of MAG and NAB C22:5; analytes not detected in other tissues by this method. Furthermore, as far as it can be ascertained, MAG C22:5 has not been previously reported in rat tissues. A quantitative method based on precursor ion - product ion transitions was developed based on the NABs and MAGs identified by the survey scans. By employing this method to analyze various rat tissues harvested immediately after death and five hours post mortem, quantitative data was obtained not only for a broad range of NABs and MAGs at basal levels but also an insight into postmortem changes of these analytes.